Adapting Through Responsible Consumption: Organizational Strategies for Equity and Inclusive Development - Elizabeth Emperatriz García-Salirrosas; Dany Yudet Millions-Liza; Ángel Acevedo-Duque (My University, 2026)
In Peru, where socioeconomic inequalities remain a critical challenge, responsible consumption has shifted from individual decisions to organizational strategies with the potential to reduce structural disparities. This study adopted an exploratory–descriptive qualitative design to gain an in-depth understanding of organizational initiatives for responsible consumption and their contributions to social equity. Using documentary analysis, the READ protocol (Read, Extract, Analyze, Distill) was applied to systematically examine public information from 104 Perú Sustainable-affiliated organizations across 16 economic sectors. The analysis identified six categories of initiatives: eco-efficient management, circular economy, sustainable supply chains, education and awareness, sustainable products, and green financing that are linked to five dimensions of equity: economic inclusion, access to essential services, gender equality, inclusion of vulnerable populations, and capacity building. The circular economy (54.8%) and sustainable supply chains stood out for their greater potential to include vulnerable groups by integrating them into formal value chains. The reported impacts ranged from 100 to over one million beneficiaries, in addition to environmental reductions of 30–50%, although methodological heterogeneity limited comparability. Financial constraints (67.3%), along with cultural resistance and institutional barriers, were identified as the main obstacles. Overall, the findings show that responsible organizational consumption can be an effective mechanism for reducing inequality if designed using systemic and integrated approaches, reinforcing the need for public policies, specialized financial instruments, and regulatory frameworks that enhance its transformative impact in favor of inclusive development in the country.
Keywords: Equity (law); Sustainable development; Transformative learning; Public economics; Business; Inequality; Socioeconomic status; Consumption (sociology); Economics; Inclusion (mineral); Social equality; Financial inclusion; Inclusive growth; Sustainable consumption; Economic growth; Socioeconomic development; Organizational structure; Organizational economics; Poverty; Social justice; Environmental resource management; Inclusive development; Intergenerational equity; Marketing; Value (mathematics); Public sector; Public relations; Mainstreaming; Organizational culture; Economic system; Environmental economics; Population; Public policy; Sustainability; Economic inequality; Equity (law); Sustainable development; Transformative learning; Inequality; Socioeconomic status; Consumption (sociology); Inclusion (mineral); Social equality; Financial inclusion; Social Sciences Business, Management and Accounting Business and International Management Innovation and Socioeconomic Development; Social Sciences Business, Management and Accounting Marketing Environmental Sustainability in Business; Social Sciences Business, Management and Accounting Strategy and Management Corporate Social Responsibility Reporting